Efficient entrapment and catalytic conversion of lithium polysulfides on hollow metal oxide submicro-spheres as lithium–sulfur battery cathodes. Issue 12 (12th March 2018) - Ma, Feng; Liang, Jiashun; Wang, Tanyuan; Chen, Xian; Fan, Yining; Hultman, Benjamin; Xie, Huan; Han, Jiantao; Wu, Gang; Li, Qing
Abstract : Hollow structured metal oxide (Co3 O4, Mn2 O3, and NiO) submicro-spheres are prepared by a novel method and employed as efficient LiPS immobilizers. Abstract : Li–S battery technology, with high theoretical capacity and energy density, has drawn much attention in recent years as a possible replacement for current Li-ion battery technologies. A major drawback of Li–S batteries is a severe capacity fading effect which, to a large extent, stems from the dissolution and diffusion of lithium polysulfides (LiPS) that are formed during both charge and discharge cycles. The self-discharge caused by the LiPS migration during the charge process (the so-called "shuttle effect") often leads to the capacity decay of Li–S batteries. Herein, hollow structured metal oxide (Co3 O4, Mn2 O3, and NiO) submicro-spheres are prepared by a novel method and employed as efficient LiPS immobilizers. These Li–S batteries, based on the developed metal oxide spheres, possess outstanding rate capability and cycling stability. The best performing S/C/Co3 O4 electrode delivers excellent cycling stability with only a 0.066% capacity decay per cycle during 550 cycles. Moreover, its discharge capacity is as high as 428 mA h g −1 at a 3C rate which is far superior to that of bare S/C (115 mA h g −1 ) at 3C. The fast kinetics of the electrocatalytic conversion of LiPS on the developed Co3 O4 electrode and its unique hollow structure are the key factors that lead to its outstanding performance as a Li–S battery cathode material.